Martienssen, Rex Distin. Martienssen House, Greenside. 14-04-1940. Door and frame details - Martienssen, Rex Distin; Martienssen, Rex Distin (My University, 2011)
Martienssen, Rex Distin.Martienssen House Greenside. 14-04-1940. Door and frame details. Ink on paper.
Ink on paper. 760x545 and 545x755
Keywords: Martienssen, Rex Distin. Martienssen House, Greenside. 14-04-1940 Door and frame details 760x545 & 545x755; Martienssen, Rex Distin. Martienssen House, Greenside. 14-04-1940 Door and frame details 760x545 & 545x755